Strategies for the prevention of malaria in pregnancy in Indonesia in the COVID-19 pandemic era - Prawira-Putra, Andre; Lukito, Theda; Ahmed, Rukhsana (International Journal Of Community Medicine And Public Health, 2020)
Malaria is one of the oldest infectious disease that continues to affect annually more than 200 million people globally. Pregnant women are the second most vulnerable group to malaria, besides children. A pregnant woman with malaria risks detrimental harm to herself and to her child resulting in adverse pregnancy outcomes. These adverse outcomes contribute to maternal, neonatal and infant morbidity and mortality. It is essential to protect pregnant women from malaria to improve the public health burden in malaria endemic countries.